ANALYSIS OF SOURCES AND USE OF WORKING CAPITAL AT PT. BLUEBIRD TBK. YEAR 2020-2022 - Sayyid Abdul Maulana Al Habsy; Hervina, Riska; Herlisa Triana; Zulkipli, Zulkipli; Syafrinadina, Syafrinadina (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2024)
This research aims to analyze the sources and use of PT Blue Bird Tbk's working capital during the 2020-2022 period. As one of the largest transportation companies in Indonesia, PT Blue Bird Tbk faces significant challenges in managing working capital, especially in the midst of economic uncertainty so that it can survive for decades. This research uses a quantitative descriptive method with a case study approach. Secondary data was obtained from PT Blue Bird Tbk's financial reports published during the 2020-2022 period. Analysis is carried out using financial ratios and comparative analysis to identify changes and trends in sources and uses of working capital. The results of the analysis show that PT Blue Bird Tbk's sources and working capital are balanced, although there was a decline around 2020, but in the following years it has become more stable and the sources and use of cash capital are balanced and to increase cash flow. This research concludes that the Company has succeeded in adjusting financial strategy with existing conditions, utilizing various sources of working capital to ensure operational continuity. However, continuous improvements in cash flow management and operational efficiency are still needed to face future challenges.